WaMn1 - aox Catalysts Synthesized by a One-Step Urea Co-precipitation Method for Selective Catalytic Reduction of NOx with NH3 at Low Temperatures - Sun, W.; Li, Xin Yong; Zhao, Q.; Tade, M.; Liu, Shaomin (American Chemical Society, 2016)
Selective catalytic reduction (SCR) of NOx with NH3 (NH3-SCR) at low temperatures is a promising technology for DeNOx (removal of NOx) as a result of its high NOx conversion, excellent selectivity, and broad application prospect. As a result of the remarkable activity under low temperature for SCR performance, Mn-based catalysts have attracted extensive attention. In this work, a series of WαMn1 – αOx (α = 0, 0.25, 0.33, 0.5, or 1) catalysts were synthesized by a one-step urea co-precipitation method and characterized by X-ray diffraction, Raman, X-ray photoelectron spectroscopy, thermogravimetric analysis, and scanning electron microscopy. Thereamong, the W0.33Mn0.66Ox catalyst showed the highest NH3-SCR activity within a broad temperature range of 230–470 °C. In addition, the active Mn and W species were in highly amorphous or poorly crystalline states. It was revealed that the interaction of W and Mn increased the chemistry oxygen content of the catalysts, thus enhancing the low-temperature SCR performance.